Negative electrode slurry and preparation method thereof, negative electrode plate and lithium ion battery

By using isopropyl alcohol, propylene glycol and propylene alcohol as surface tension regulators in the negative electrode slurry of lithium-ion batteries, the problems of vertical marking and cracking during the coating of the negative electrode sheet are solved, and the battery performance and production efficiency are improved while avoiding the use of isopropyl alcohol, propylene glycol and propylene alcohol as surface tension regulators. Environmental pollution.

CN119297282AInactive Publication Date: 2025-01-10EVE ENERGY CO LTD

Patent Information

Application Number
CN202411321226.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The negative electrode sheets of existing lithium-ion batteries are prone to vertical marks and cracks during the coating process, resulting in poor appearance, increased resistance, and smaller peeling force, which affects battery performance. Common additives have problems such as environmental pollution and deterioration of battery performance.

Method used

Isopropanol, propylene glycol and propylene alcohol are used as surface tension regulators to add to the negative electrode slurry to adjust the surface tension after coating, reduce drying temperature, reduce energy consumption and pollution, and mix and stir directly through a simple preparation method. , a negative electrode slurry with a low residual amount is formed.

Benefits of technology

It effectively improves the appearance quality of the negative electrode sheet, improves the production yield and efficiency, avoids degradation of battery performance and environmental pollution, and ensures the circulation and safety performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297282A_ABST
    Figure CN119297282A_ABST
Patent Text Reader

Abstract

The invention discloses negative electrode slurry and a preparation method thereof, a negative electrode plate and a lithium ion battery, the negative electrode slurry comprises a negative electrode material, the negative electrode material comprises a negative electrode active substance with the mass content of 85%-98% and a surface tension regulator with the mass content of 0.1%-5%, the surface tension regulator is at least two of isopropanol, propylene glycol and allyl alcohol. According to the invention, the problem of vertical lines and even cracking during coating of the pole piece can be improved, the cycle performance and the safety performance of the battery are ensured, and meanwhile, environmental pollution is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium batteries, and in particular to a negative electrode slurry and a preparation method thereof, a negative electrode sheet and a lithium ion battery. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density, low self-discharge, long cycle life, safety and environmental protection, and are therefore widely used in consumer electronics, electric vehicles, power and communication energy storage and other fields. Consumer batteries refer to capacity-type lithium-ion batteries represented by 3C products such as mobile phones, tablets, and laptops. They started early in the lithium-ion battery industry and have always occupied an important position. In recent years, with the improvement of the national economic level and residents' consumption capacity, the market has higher and higher requirements for the energy density of consumer batteries, which has led to an increase in the content and coating amount of active substances in the pole pieces, resulting in an increase in the thickness of the pole pieces, which is prone to vertical lines or even cracks during the drying process, and marks may also appear during subsequent rolling, which directly affects the appearance and quality of the pole pieces, causing the pole pieces to lose powder, increase resistance, and reduce peeling force, etc., causing the battery performance to decline rapidly.

[0003] In order to improve the problem of vertical lines or even cracks on the pole piece during the coating process, there are currently two main methods. One is to improve the coating process and adjust the parameters of the oven and wind frequency during the coating and drying process, including oven temperature, belt speed, wind speed, and air outlet position. However, this method has a limited scope of improvement and cannot completely solve the problem of vertical lines caused by slurries with large surface tension and poor wettability. Another method is to improve the formulation of the slurry by adding additives to adjust the interfacial tension during the homogenization process to reduce the problem of uneven tension caused by different drying speeds in different areas of the pole piece, thereby improving the problems of vertical lines, cracking, and curling after high-temperature drying of the pole piece.

[0004] At present, the additives for improving the vertical lines and cracking of the pole pieces mainly include N-methylpyrrolidone (NMP), ethylene carbonate (EC) and 1,3-butanediol. For example, Chinese patent CN114335528A discloses adding N-methylpyrrolidone to the negative electrode slurry to solve the problem of coating cracking of the negative electrode piece. However, the recovery rate of N-methylpyrrolidone is low during the drying process, and it is a toxic and harmful organic solvent, which will cause pollution to the environment. Chinese patent CN109841789A discloses a process for improving the coating cracking of the aqueous negative electrode piece of a lithium-ion battery, and the problem of coating cracking of the aqueous negative electrode piece can be effectively improved by adding a small amount of ethylene carbonate. However, the high residual amount of ethylene carbonate in the pole piece will lead to an increase in the local viscosity of the electrolyte in the pole piece. At the same time, its water absorption characteristics will cause the lithium salt to react with water during exhaust, deteriorating the battery performance. In addition, ethylene carbonate needs to be melted in advance during the homogenization process, which undoubtedly adds a process to the battery production. Chinese patent CN110459773A discloses that adding 1,3-butanediol can reduce the hardness and brittleness of the pole piece, thereby improving the problem of easy breakage of the pole piece during processing and use. However, 1,3-butanediol has a high boiling point and a large residual amount, which will increase the interface impedance in the battery and deteriorate the battery's later cycle performance.

[0005] Therefore, there is an urgent need to develop a method to improve the vertical lines or even cracks produced by electrode coating to solve the problem of poor electrode appearance without affecting the battery cycle performance and safety performance, so as to meet the market demand for consumer batteries. Summary of the invention

[0006] In order to improve the problem of vertical lines or even cracks in the electrode coating, ensure the cycle performance and safety performance of the battery, and avoid environmental pollution, the present application provides a negative electrode slurry and a preparation method thereof, a negative electrode sheet and a lithium-ion battery.

[0007] In a first aspect, the present application provides a negative electrode slurry, which adopts the following technical solution:

[0008] A negative electrode slurry comprises: a negative electrode material, wherein the negative electrode material comprises 85%-98% by mass of a negative electrode active material and 0.1%-5% by mass of a surface tension regulator, wherein the surface tension regulator is at least two of isopropyl alcohol, propylene glycol and allyl alcohol.

[0009] At least two of isopropanol, propylene glycol and propylene alcohol are used as surface tension regulators, which have the advantages of stable properties, low boiling point and not easy to remain. First, adding them to the negative electrode slurry can improve the wettability of the negative electrode slurry, thereby effectively reducing the surface tension of the negative electrode slurry after coating, so as to improve the problem of vertical lines or even cracks in the coating; second, isopropanol, propylene glycol and propylene alcohol are easy to volatilize during the drying process, and the residual amount is low, which can not only reduce the drying temperature and energy consumption, but also reduce pollution to the environment. In this way, the addition of the surface tension regulator can not only effectively improve the problem of vertical lines or even cracks in the coating, but also its residual amount is low, avoiding side reactions with the electrolyte, thereby avoiding deterioration of battery performance.

[0010] Preferably, the surface tension regulator is a mixture of isopropanol and propylene glycol with a mass content of 1.5%-2.5%, and the mass ratio of the isopropanol to the propylene glycol is 4:6-7:3.

[0011] The combination of isopropyl alcohol and propylene glycol is beneficial to improving the vertical lines and even cracks on the pole pieces. On this basis, adding a moderate amount of isopropyl alcohol can improve the leveling of the negative electrode slurry, making the surface tension of the negative electrode slurry moderate to ensure the coating quality; and adding a moderate amount of surface tension regulator is more conducive to improving the vertical lines and even cracks on the pole pieces.

[0012] Preferably, the surface tension regulator is a mixture of isopropanol and propylene glycol with a mass content of 2%, and the mass ratio of isopropanol to propylene glycol is 1: 1. In this way, the negative electrode slurry coating and drying can avoid the generation of vertical lines, and the residual amount of the surface tension regulator is extremely low, which can ensure the cycle performance and safety performance of the battery on the basis of ensuring the coating quality of the negative electrode sheet.

[0013] Preferably, the negative electrode material further comprises a conductive agent with a mass content of 0.01%-1%, a binder with a mass content of 0.1%-5%, and a thickener with a mass content of 0.1%-5%.

[0014] Preferably, the negative electrode active material is at least one of artificial graphite and natural graphite;

[0015] The conductive agent is at least one of carbon black, conductive graphite and carbon fiber;

[0016] The binder is at least one of cellulose, styrene-butadiene rubber and modified styrene-butadiene rubber;

[0017] The thickener is at least one of sodium carboxymethyl cellulose and lithium carboxymethyl cellulose.

[0018] In a second aspect, the present application provides a method for preparing a negative electrode slurry, which adopts the following technical solution:

[0019] A method for preparing a negative electrode slurry, the method for preparing the negative electrode slurry comprises the following steps:

[0020] S1. After mixing the thickener and water at a low speed for a period of time, stirring at a high speed under vacuum to obtain a glue solution;

[0021] S2. After mixing the formulated amount of conductive agent and the formulated amount of negative electrode active material at low temperature and stirring for a period of time, mix with a part of the glue and a certain amount of water and continue to stir at low temperature for a period of time, then add the remaining glue and the formulated amount of surface tension regulator and mix and stir at low temperature for a period of time under vacuum, then add an appropriate amount of water to adjust the viscosity, and add the formulated amount of binder and continue to mix and stir at low temperature to obtain the negative electrode slurry.

[0022] The preparation method has a simple process, and the surface tension regulator does not need to be pretreated, so it can be directly added to be mixed and stirred with other raw materials, which greatly reduces the difficulty and cost of preparing the negative electrode slurry.

[0023] Preferably, in S1, the thickener and water in the formula amount are mixed in a mass ratio of (1.5%-2%): 100%, and after low-speed stirring at an orbital speed of 10-50 rpm and a dispersion speed of 500-3000 rpm for 10-60 min, the thickener on the stirring shaft is scraped off, and then high-speed stirring is carried out at an orbital speed of 10-50 rpm and a dispersion speed of 500-3000 rpm for 100-300 min under a vacuum state to obtain the glue solution.

[0024] Preferably, in S2, the conductive agent and the negative electrode active material are stirred for 10-100 min at a revolution speed of 10-50 rpm and a dispersion speed of 500-2000 rpm under cooling water, and then 20%-30% of the glue prepared in S1 and water are added in a mass ratio of (0.8-1.1):1, and the amount of water added is 20%-30% of the total water amount, and the conductive agent and the negative electrode active material are stirred for 10-100 min at a revolution speed of 10-50 rpm and a dispersion speed of 500-2000 rpm under cooling water. After stirring at a dispersed speed for 10-60 minutes, scrape the cylinder; then add the remaining glue and the formulated amount of surface tension regulator, and stir for 10-300 minutes at a revolution speed of 10-50rpm and a dispersion speed of 500-3000rpm under vacuum; then add an appropriate amount of water to adjust the viscosity to 2000-4000cp, and add the formulated amount of binder and continue stirring at a revolution speed of 10-50rpm and a dispersion speed of 500-2000rpm for 10-60 minutes to obtain the negative electrode slurry.

[0025] In a third aspect, the present application provides a negative electrode sheet, which adopts the following technical solution:

[0026] A negative electrode sheet comprises: a negative electrode current collector, at least one surface of which is provided with a negative electrode active material layer, and the negative electrode active material layer is prepared by using the negative electrode slurry.

[0027] The negative electrode sheet has a small number of vertical lines or even no vertical lines on its surface, which improves the appearance quality of the negative electrode sheet and increases the production yield and production efficiency of the negative electrode sheet.

[0028] In a fourth aspect, the present application provides a lithium-ion battery, which adopts the following technical solution:

[0029] A lithium ion battery comprises a positive electrode sheet, a separator, an electrolyte and the negative electrode sheet.

[0030] The lithium-ion battery of the present application has good electrochemical performance, avoids environmental pollution, and meets the market demand for consumer batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1A A schematic diagram of a negative electrode sheet prepared in Example 9;

[0032] Figure 1B A schematic diagram of the negative electrode sheet prepared in Example 1;

[0033] Figure 1C A schematic diagram of a negative electrode sheet prepared in Example 10;

[0034] Figure 2 The viscosity change diagram of the negative electrode slurry prepared in Examples 1-4 and Comparative Examples 1-3 within 24 hours;

[0035] Figure 3 The cycle data of the lithium-ion batteries prepared in Examples 1-4 and Comparative Examples 1-3 at 25°C are shown. DETAILED DESCRIPTION

[0036] For better understanding and implementation, the technical solution of the present invention will be clearly and completely described below in conjunction with embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.

[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0038] Unless otherwise indicated, all numerical values ​​expressing quantities of ingredients, reaction conditions, and so forth used in the specification and claims are to be understood as modified by the term “about.” Accordingly, unless indicated to the contrary, the numerical parameters set forth herein are approximations that can vary depending upon the desired properties desired to be obtained.

[0039] As used herein, "and / or" means one or all of the mentioned elements.

[0040] As used herein, “including” and “comprising” encompasses the case where only the stated elements are present as well as the case where there are other elements other than the stated elements.

[0041] All percentages in the present invention are by weight, unless otherwise specified.

[0042] Unless otherwise indicated, "a", "an", "an" and "the" used in this specification are intended to include "at least one" or "one or more". For example, "a component" means one or more components, so more than one component may be considered and may be employed or used in the implementation of the embodiment.

[0043] Example 1

[0044] 1. Preparation of negative electrode slurry

[0045] A negative electrode slurry is prepared by the following steps:

[0046] S1. A thickener sodium carboxymethyl cellulose having a mass content of 1% and a solvent water were mixed in a mass ratio of 2%:100%, and the mixture was stirred at a low speed of 25 rpm and a dispersion speed of 1000 rpm for 30 min, and the thickener on the stirring shaft was scraped off, and then stirred at a high speed of 40 rpm and a dispersion speed of 2500 rpm for 200 min under a vacuum state to obtain the glue solution;

[0047] S2. After stirring 0.5% by mass of conductive graphite, a conductive agent, and 95.5% by mass of natural graphite, a negative electrode active material, at a revolution speed of 25 rpm and a dispersion speed of 1000 rpm for 50 minutes under cooling water, 25% of the glue obtained in S1 and water in a mass ratio of 0.9:1 are added, and the amount of water added is 25% of the total water volume. After stirring for 30 minutes at a revolution speed of 25 rpm and a dispersion speed of 1000 rpm under cooling water, the cylinder is scraped; then the remaining glue and a surface tension regulator with a mass content of 2%, i.e., isopropanol and propylene glycol with a mass ratio of 1:1, are added, and stirred for 200 minutes at a revolution speed of 30 rpm and a dispersion speed of 2000 rpm under vacuum; then an appropriate amount of water is added to adjust the viscosity to 3000 cp, and a binder with a mass content of 1% is added and stirred for 30 minutes at a revolution speed of 25 rpm and a dispersion speed of 1000 rpm to obtain the negative electrode slurry.

[0048] 2. Preparation of negative electrode

[0049] The negative electrode slurry is passed through a 200-mesh sieve and then coated on a copper foil current collector, and then dried, rolled, cut and slit to obtain a negative electrode sheet.

[0050] 3. Preparation of positive electrode

[0051] A binder PVDF with a mass content of 1% and a solvent N-methylpyrrolidone are mixed and stirred to obtain a glue solution, and then a conductive agent, namely a single-walled carbon nanotube with a mass content of 0.05%, a multi-walled carbon nanotube with a mass content of 0.2% and a Super-P with a mass content of 0.55%, is added, and a lithium cobalt oxide positive electrode material with a mass content of 98.2% and an appropriate amount of solvent N-methylpyrrolidone are added and mixed and stirred to obtain a positive electrode slurry; the positive electrode slurry is passed through a 200-mesh sieve and then coated on an aluminum foil current collector, and a positive electrode sheet is obtained after drying, rolling, cutting and slitting.

[0052] 4. Preparation of Diaphragm

[0053] A polyethylene film is used as a base film, and coating layers are coated on two opposite surfaces of the base film. The coating layers are a 2μm thick aluminum oxide ceramic layer close to the base film and a 1μm thick PVDF adhesive layer coated on the ceramic layer, so as to obtain a composite diaphragm with a thickness of 6μm.

[0054] 5. Preparation of Electrolyte

[0055] Ethylene carbonate, propylene carbonate and propyl propionate are mixed uniformly in a mass ratio of 1:1:1 to obtain an organic solvent; 1 mol / L LiPF6 is added to the organic solvent and stirred until it is completely dissolved, and then 2 wt % of fluoroethylene carbonate is added and stirred uniformly to obtain an electrolyte.

[0056] 6. Preparation of Lithium-ion Batteries

[0057] The negative electrode sheet, the positive electrode sheet and the composite separator are wound to obtain a core, the core is placed in a shell, the electrolyte is injected, and then a lithium-ion battery is obtained through packaging, formation and capacity separation processes.

[0058] Example 2

[0059] The difference between this embodiment and embodiment 1 is that the surface tension regulator is a mixture of isopropanol and propenol in a mass ratio of 1:1, and the remaining steps and parameter settings are consistent with those in embodiment 1.

[0060] Example 3

[0061] The difference between this embodiment and embodiment 1 is that the surface tension regulator is a mixture of propylene glycol and allyl alcohol in a mass ratio of 1:1, and the remaining steps and parameter settings are consistent with those in embodiment 1.

[0062] Example 4

[0063] The difference between this embodiment and embodiment 1 is that the surface tension regulator is a mixture of isopropanol, propylene alcohol and propylene glycol in a mass ratio of 1:1:1, and the remaining steps and parameter settings are consistent with those in embodiment 1.

[0064] Example 5

[0065] The difference between this embodiment and embodiment 1 is that the surface tension regulator is a mixture of isopropanol and propylene glycol in a mass ratio of 9:1, and the remaining steps and parameter settings are consistent with those in embodiment 1.

[0066] Example 6

[0067] The difference between this embodiment and embodiment 1 is that the surface tension regulator is a mixture of isopropanol and propylene glycol in a mass ratio of 7:3, and the remaining steps and parameter settings are consistent with those in embodiment 1.

[0068] Example 7

[0069] The difference between this embodiment and embodiment 1 is that the surface tension regulator is a mixture of isopropanol and propylene glycol in a mass ratio of 4:6, and the remaining steps and parameter settings are consistent with those in embodiment 1.

[0070] Example 8

[0071] The difference between this embodiment and embodiment 1 is that the surface tension regulator is a mixture of isopropanol and propylene glycol in a mass ratio of 2:8, and the remaining steps and parameter settings are consistent with those in embodiment 1.

[0072] Example 9

[0073] The difference between this embodiment and embodiment 1 is that the mass content of the surface tension regulator is 1.5%, and the other steps and parameter settings are consistent with those in embodiment 1.

[0074] Example 10

[0075] The difference between this embodiment and embodiment 1 is that the mass content of the surface tension regulator is 2.5%, and the other steps and parameter settings are consistent with those of embodiment 1.

[0076] Comparative Example 1

[0077] The difference between this comparative example and Example 1 is that the surface tension regulator is N-methylpyrrolidone, and the other steps and parameter settings are consistent with Example 1.

[0078] Comparative Example 2

[0079] The difference between this comparative example and Example 1 is that the surface tension regulator is ethylene carbonate, and the other steps and parameter settings are consistent with Example 1.

[0080] Comparative Example 3

[0081] The difference between this comparative example and Example 1 is that the surface tension regulator is 1,3-butanediol, and the other steps and parameter settings are consistent with Example 1.

[0082] The above embodiments are only preferred embodiments of the present invention. The present invention cannot list all the embodiments one by one, so embodiments 1-10 and comparative examples 1-3 are used as examples for description.

[0083] See also Figure 1A The mass content of the surface tension regulator in Example 9 is 1.5%, and the surface of the prepared negative electrode sheet has no cracks but slight vertical lines. Figure 1B The mass content of the surface tension regulator in Example 1 is 2%, and the surface of the prepared negative electrode sheet has no cracks and no vertical lines. Figure 1C , the mass content of the surface tension regulator in Example 10 is 2.5%, and the surface of the prepared negative electrode sheet has no cracks but slight vertical lines. It can be seen that when the mass content of the surface tension regulator is 0.1%-5%, the surface of the prepared negative electrode sheet has no cracks and can improve the vertical lines. However, within this range, when the amount of surface tension regulator added is low or high, it is easy to affect the wettability and leveling of the negative electrode slurry, so that slight vertical lines will still exist. When the mass content of the surface tension regulator is 2%, the state of the negative electrode slurry is the best, and the surface of the negative electrode sheet prepared by coating is smooth and has no vertical lines.

[0084] Table 1 is a record of negative electrode slurries and coating process parameters prepared in Examples 1-4 and Comparative Examples 1-3.

[0085] Table 1

[0086]

[0087] Referring to Table 1, the negative electrode slurry prepared in Comparative Examples 1-3 has a large contact angle with the copper foil during coating, a high surface tension, and a high drying temperature, and vertical lines exist on the surface of the prepared negative electrode sheet. The negative electrode slurry prepared in Examples 1-4 has a small contact angle with the copper foil during coating, a low surface tension, and a low drying temperature, and the surface of the prepared negative electrode sheet has basically no vertical lines. It can be seen that compared with N-methylpyrrolidone, ethylene carbonate and 1,3-butanediol, the surface tension regulator of the present application can reduce the surface tension of the negative electrode slurry during coating, thereby improving the wettability and leveling of the negative electrode slurry, so that the surface of the prepared negative electrode sheet has basically no vertical lines, so as to improve the appearance quality of the negative electrode sheet and improve the production yield and production efficiency of the negative electrode sheet. In addition, the surface tension regulator of the present application is volatile, which can reduce the drying temperature and save energy consumption.

[0088] Meanwhile, by comparing Examples 1-4, it can be seen that the negative electrode slurry and negative electrode sheet prepared in Example 1 are in the best state, that is, the surface tension regulator is preferably a mixture of isopropyl alcohol and propylene glycol.

[0089] Table 2 is a record of negative electrode slurries and coating process parameters prepared in Example 1 and Examples 5-8.

[0090] Table 2

[0091]

[0092] Referring to Table 2, the negative electrode slurry prepared in Example 1 has a moderate contact angle with the copper foil during coating, moderate surface tension, and a low drying temperature, and the prepared negative electrode sheet has no cracks and no vertical lines. The negative electrode slurry prepared in Example 5 has a small contact angle with the copper foil during coating, low surface tension, and a high drying temperature, and the prepared negative electrode sheet has slight cracks and vertical lines. The negative electrode slurry prepared in Example 6 has a small contact angle with the copper foil during coating, low surface tension, and a low drying temperature, and the prepared negative electrode sheet has no cracks and no vertical lines. The negative electrode slurries prepared in Examples 7-8 have a large contact angle with the copper foil during coating, high surface tension, and a low drying temperature, and the prepared negative electrode sheets have no cracks and no vertical lines.

[0093] It can be seen that, based on the surface tension regulator being preferably a mixture of isopropanol and propylene glycol, the mass ratio of isopropanol to propylene glycol is 1:1, and the state of the negative electrode slurry and negative electrode sheet prepared is the best. When the content of isopropanol is low, the surface tension of the negative electrode slurry is high, which is not conducive to the efficient and high-quality coating of the negative electrode slurry. As the content of isopropanol increases, the surface tension of the negative electrode slurry continues to decrease. Too low surface tension will cause the leveling of the negative electrode slurry to become greater, thereby affecting the coating quality, and even causing cracks on the surface of the negative electrode sheet and producing vertical lines.

[0094] Test Method

[0095] 1. Surface tension regulator residual rate test

[0096] The negative electrode sheets coated and dried in Examples 1-4 and Comparative Examples 1-3 were respectively subjected to surface powder scraping, and then the residual surface tension regulator in the powder was dissolved and extracted with ethanol. After sufficient standing, the content of the surface tension regulator in the supernatant was tested by GCMS. According to the standard addition method, standard curves of different surface tension regulators were prepared to obtain the content of the surface tension regulator, and the residual rate of the surface tension regulator was calculated according to the added amount of the surface tension regulator.

[0097] 2. Cycle performance test

[0098] The lithium ion batteries prepared in Examples 1-4 and Comparative Examples 1-3 were subjected to cycle performance tests. The test method was as follows: at 25°C, the voltage range was The rate is 1.3C / 1C, and 0.5C and 0.2C low current charging and discharging are performed every 50 cycles.

[0099] Test Results

[0100] Table 3 shows the results of the thixotropic value of the negative electrode slurry, the negative electrode sheet peeling force and the residual rate of the surface tension regulator in the lithium ion batteries prepared in Examples 1-4 and Comparative Examples 1-3.

[0101] Table 3

[0102]

[0103] Referring to Table 3, according to the test results of the residual amount and residual rate of the surface tension regulator, the surface tension regulators of Comparative Examples 1-3 have more residues after drying, especially the residual rates of the surface tension regulators of Comparative Examples 2 and 3 are extremely high. These residual surface tension regulators are very likely to have side reactions with the electrolyte, thereby deteriorating the cycle performance of the lithium ion battery. For example, a higher residual amount of ethylene carbonate will increase the local viscosity of the electrolyte, and the water absorption characteristics of ethylene carbonate will also cause the lithium salt to react with water when the lithium ion battery is vented, thereby deteriorating the cycle performance of the lithium ion battery. The surface tension regulators of Examples 1-4 have a lower boiling point and a residual rate of only 0.8%-1.2%, that is, the surface tension regulator is basically completely volatilized during the drying process of the negative electrode sheet, which can effectively avoid the adverse effects of the residual surface tension regulator on the performance of the lithium ion battery.

[0104] Combination Figure 2 , from the analysis of the thixotropic value of the negative electrode slurry, the negative electrode slurry with a large thixotropic value tends to show a large viscosity change under shear, thereby affecting the fluidity and uniformity during the coating process, resulting in uneven coating problems. The surface tension regulator added in Comparative Examples 2 and 3 causes the thixotropic value of the negative electrode slurry to be extremely large, so that the prepared negative electrode slurry undergoes a large viscosity change over a period of time, which is not only not conducive to the coating of the negative electrode slurry. Combined with Table 1, vertical lines will also appear on the surface of the negative electrode sheet prepared in Comparative Examples 2 and 3. The surface tension regulator added in Example 1 and Example 4 can significantly reduce the thixotropic value of the negative electrode slurry, thereby improving the thixotropy of the negative electrode slurry to improve the coating effect of the negative electrode slurry. That is, the surface tension regulator added in Example 1 and Example 4 can improve the stability of the negative electrode slurry, and the viscosity of the negative electrode slurry changes very little, which is beneficial to improving the coating quality and the yield rate of the negative electrode sheet.

[0105] From the perspective of the peeling force of the negative electrode sheet, the peeling force of Example 1 and Example 4 is slightly improved, which can improve the problem of powder falling of the negative electrode sheet, thereby improving the electrochemical performance of the lithium-ion battery.

[0106] Table 4 shows the capacity, internal resistance and cycle performance results of the lithium ion batteries prepared in Examples 1-4 and Comparative Examples 1-3.

[0107] Table 4

[0108] plan Internal resistance(mΩ) Capacity (mAh) Capacity retention rate after 800 cycles at 25℃ Example 1 16.24 5010 91.60% Example 2 16.45 5014 89.63% Example 3 16.30 5013 90.23% Example 4 16.19 5017 90.38% Comparative Example 1 16.36 5016 88.56% Comparative Example 2 16.52 5018 90.02% Comparative Example 3 16.63 5004 88.03%

[0109] Referring to Table 4, there is no significant difference in the internal resistance and initial capacity of the lithium ion batteries prepared in Examples 1-4 and Comparative Examples 1-3, which shows that the addition of the surface tension regulator has little effect on the internal resistance and capacity of the lithium ion battery.

[0110] On this basis, combined with Figure 3It can be seen that the addition of the surface tension regulator 1,3-butanediol in comparative example 3 makes the performance of the lithium-ion battery gradually deteriorate after 400 cycles, the capacity decreases greatly after 750 cycles, and there is a trend of cycle diving at 800 cycles. This shows that the addition of 1,3-butanediol is easy to deteriorate the cycle performance of the battery. At the same time, the addition of N-methylpyrrolidone in comparative example 1 will also have a bad effect on the cycle performance of the lithium-ion battery, causing the performance of the lithium-ion battery to gradually deteriorate after 500 cycles. In comparison, the lithium-ion batteries of Examples 1-4, especially Example 1, have better cycle performance, a relatively stable cycle trend, and a capacity retention rate that is improved to a certain extent compared to comparative examples 1-3. In addition, when the surface regulator is a mixture of isopropanol and propylene glycol with a mass content of 2% and a mass ratio of 1:1, the cycle performance of the lithium-ion battery is the best.

[0111] In summary, the surface tension regulator provided by the present application can effectively improve the wettability of the negative electrode slurry, thereby adjusting the interfacial tension during the homogenization process, improving the affinity of the negative electrode active material and the binder, and improving the kinetic process of solvent volatilization during the drying process of the negative electrode slurry in the high surface density coating process, and reducing the problem of uneven surface tension caused by different drying speeds in different regions of the negative electrode sheet, thereby improving the problems of cracking, vertical lines, and poor flexibility of the negative electrode sheet after high temperature drying, and improving the yield rate and production efficiency of the negative electrode sheet. At the same time, the surface tension regulator can also improve the thixotropy of the negative electrode slurry, improve the stability of the negative electrode slurry, and then improve the coating effect of the negative electrode slurry. In addition, the residual rate of the surface tension regulator in the negative electrode sheet is low, which can reduce the possibility of side reactions with the electrolyte, avoid deteriorating the cycle performance of the lithium ion battery, and improve the electrochemical performance of the lithium ion battery.

[0112] In addition, the surface tension regulator provided in the present application does not need to be pretreated during the preparation of the negative electrode slurry, and the process is simple and the cost is low.

[0113] It should be noted that although the test results of Comparative Example 1 are better than those of Comparative Example 2 and Comparative Example 3, Comparative Example 1 still has the defects that the negative electrode slurry has a high thixotropic value, which is not conducive to coating and easily produces vertical lines, and a large amount of surface tension regulator residue affects the electrochemical performance of the lithium-ion battery. In addition, the surface tension regulator N-methylpyrrolidone in Comparative Example 1 is a toxic and harmful organic solvent, which is easy to pollute the environment at a high residual rate, thereby limiting its use.

[0114] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.

Claims

1. A negative electrode slurry, characterized in that: include: The negative electrode material comprises 85%-98% by mass of a negative electrode active material and 0.1%-5% by mass of a surface tension regulator, wherein the surface tension regulator is at least two of isopropyl alcohol, propylene glycol and allyl alcohol.

2. The negative electrode slurry according to claim 1, characterized in that: The surface tension regulator is a mixture of isopropanol and propylene glycol with a mass content of 1.5%-2.5%, and the mass ratio of the isopropanol to the propylene glycol is 4:6-7:

3.

3. The negative electrode slurry according to claim 2, characterized in that: The surface tension regulator is a mixture of isopropanol and propylene glycol with a mass content of 2%, and the mass ratio of the isopropanol to the propylene glycol is 1:

1.

4. The negative electrode slurry according to any one of claims 1 to 3, characterized in that: The negative electrode material further comprises a conductive agent with a mass content of 0.01%-1%, a binder with a mass content of 0.1%-5%, and a thickener with a mass content of 0.1%-5%.

5. The negative electrode slurry according to claim 4, characterized in that: The negative electrode active material is at least one of artificial graphite and natural graphite; The conductive agent is at least one of carbon black, conductive graphite and carbon fiber; The binder is at least one of cellulose, styrene-butadiene rubber and modified styrene-butadiene rubber; The thickener is at least one of sodium carboxymethyl cellulose and lithium carboxymethyl cellulose.

6. A method for preparing a negative electrode slurry, characterized in that: The preparation method is used to prepare the negative electrode slurry according to any one of claims 1 to 5, and the preparation method comprises the following steps: S1. After mixing the thickener and water at a low speed for a period of time, stirring at a high speed under vacuum to obtain a glue solution; S2. After mixing the formulated amount of conductive agent and the formulated amount of negative electrode active material at low temperature and stirring for a period of time, mix with a part of the glue and a certain amount of water and continue to stir at low temperature for a period of time, then add the remaining glue and the formulated amount of surface tension regulator and mix and stir at low temperature for a period of time under vacuum, then add an appropriate amount of water to adjust the viscosity, and add the formulated amount of binder and continue to mix and stir at low temperature to obtain the negative electrode slurry.

7. The method for preparing negative electrode slurry according to claim 6, characterized in that: In the S1, the thickener and water in the formula amount are mixed according to the mass ratio (1.5%-2%): 100%, and after low-speed stirring at a revolution speed of 10-50 rpm and a dispersion speed of 500-3000 rpm for 10-60 minutes, the thickener on the stirring shaft is scraped off, and then high-speed stirring is carried out at a revolution speed of 10-50 rpm and a dispersion speed of 500-3000 rpm for 100-300 minutes under a vacuum state to obtain the glue solution.

8. The method for preparing negative electrode slurry according to claim 6, characterized in that: In the S2, the conductive agent and the negative electrode active material in the formula amount are stirred for 10-100 minutes at a revolution speed of 10-50 rpm and a dispersion speed of 500-2000 rpm under cooling water, and then 20%-30% of the glue prepared in the S1 and water are added in a mass ratio of (0.8-1.1):1, and the amount of water added is 20%-30% of the total water amount, and the conductive agent and the negative electrode active material in the formula amount are stirred for 10-100 minutes at a revolution speed of 10-50 rpm and a dispersion speed of 500-2000 rpm under cooling water. After stirring at high speed for 10-60 minutes, scrape the cylinder; then add the remaining glue and the formulated amount of surface tension regulator, stir for 10-300 minutes at a revolution speed of 10-50rpm and a dispersion speed of 500-3000rpm under vacuum; then add an appropriate amount of water to adjust the viscosity to 2000-4000cp, and add the formulated amount of binder and continue stirring for 10-60 minutes at a revolution speed of 10-50rpm and a dispersion speed of 500-2000rpm to obtain the negative electrode slurry.

9. A negative electrode sheet, characterized in that: include: A negative electrode current collector, wherein at least one surface of the negative electrode current collector is provided with a negative electrode active material layer, and the negative electrode active material layer is prepared by using the negative electrode slurry according to any one of claims 1 to 5.

10. A lithium ion battery, characterized in that: include: A positive electrode sheet, a separator, an electrolyte and the negative electrode sheet as claimed in claim 9.

Citation Information

Patent Citations

  • Improved process for coating cracking of aqueous negative electrode sheet of lithium-ion battery

    CN109841789A

  • Negative electrode glue solution as well as preparation method and application thereof

    CN114335528A

  • Negative electrode active material and preparation method thereof

    CN105591084A

  • Lithium ion battery, negative electrode, negative electrode conductive paste and preparation method of negative electrode conductive paste

    CN108598404A

  • Lithium ion battery pole piece slurry, pole piece and preparation method and application thereof

    CN110459773A

Cited By

  • Negative electrode colloidal liquid and preparation method thereof, negative electrode pole piece and lithium ion battery

    CN120727827A

  • A negative electrode colloidal solution, a preparation method thereof, a negative electrode sheet, and a lithium ion battery

    CN120727827B

  • Composite additive for lithium ion battery and application of composite additive

    CN122511903A